IDENTIFIKASI POTENSI KONFLIK PRA DAN PASCA PENDIRIAN RUMAH IBADAH DI INDONESIA DAN UPAYA UNTUK MENGATASINYA (STUDI KASUS DI KOTA DAN KABUPATEN BOGOR) - Aji, Ahmad Mukri (MIZAN: JOURNAL OF ISLAMIC LAW, 2014)
Identification of Potential Conflicts of Pre and Post Construction of Houses of Worship in Indonesia and Efforts To Handle (Case Study in the City and County of Bogor). Religion contains teachings regarding the highest and absolute truth about human existence and the instructions for safe and happy life in this world and hereafter. Religion should not be a factor and moreover a source of conflict trigger, because religion itself appears as a system of beliefs that are in a culture that was born out of the community itself. Besides religion becomes a controller for the actions of the members of society in accordance with the values of culture and religion.